Policy Lessons from the Free School Meal Program: A Comparative Study between Indonesia, Brazil, and India - Daniswara Rajendra (Jurnal Administrasi Publik, 2025)
The School Feeding Program is one of the social intervention strategies adopted by various countries to address issues of stunting, hunger, and nutritional inequality among school-aged children. This study aims to analyze and compare the policies and governance practices of school feeding programs in Indonesia, Brazil, and India in order to derive policy lessons for Indonesia. Using a qualitative approach with a cross-country comparative case study design and the CIPP evaluation model (Context, Input, Process, Product) this study evaluates the policy context, resources, implementation processes, and outcomes of the programs in each country. The research employs a descriptive qualitative method through literature review. The findings show that Brazil has developed a strong decentralized system involving local farmers, community-based monitoring mechanisms, and the use of social control technologies. India applies a centralized model supported by state governments, involving communities and local organizations in implementation, along with an effective real-time monitoring system. Indonesia, through the Free Nutritious Meal Program (MBG), is still in its early stages of implementation and faces major challenges in funding, coordination, and oversight. The study highlights the importance of strengthening legal foundations, involving local actors, integrating technology, and sharing fiscal responsibilities between central and local governments for program sustainability.Keywords; School Feeding Program; CIPP Evaluation Model; Cross-Country Comparison